Community Reading Park (TBM) Sirnarasa Village as a Medium to Increase Community Literacy Interest in Efforts to Empower the People of Sirnarasa Village - Al-Farizi, Farhan Fauzan; Bhudiman, Budy (Jurnal Pengabdian Nusantara, 2024)
(TBM) Community Reading Park is one of the centers of community learning activities which can be an alternative in facilitating access to reading materials and meeting people's information needs so that people with middle to lower economies located in remote areas whose access is difficult to reach will be easier to obtain the reading materials they need. One of the efforts that can be done in community empowerment is through Community Reading Gardens (TBM). This is supported by a statement conveyed by the Directorate of Community Education that one of the benefits of community reading gardens (TBM) is that they can increase community empowerment in various fields. Community empowerment starts from the concept or word empowerment. Etymologically, empowerment comes from the root word "power" which means strength or ability that aims to improve the quality of life of the community better in various fields. The method of service carried out by the author is by providing an understanding both individually and communally about the urgency of literacy to children, adolescents, and adults, especially reading. In addition, improvements were also made to TBM facilities in Sirnarasa Village. To attract literacy interest, the writers also held Discussion / Gathering activities together to discuss education as a form of introduction to literacy media development. In the process of creating a new Sirnarasa Village Community Reading Garden starting with the selection of places, the search for the location of literacy activities was carried out at the service post, this activity was also used to help school children in the Sirnarasa Village environment in carrying out learning activities from home. Community Reading Park (TBM) is a place/forum established and managed by both the community and the government to provide access to reading material services for the surrounding community as one of the main means of realizing the concept of lifelong learning to support the improvement of the quality of life of the surrounding community. Therefore, the target of community reading garden services is all levels of society who need reading materials to improve their literacy. Beneficiaries of community reading garden services are not limited to any age group, gender, or group; therefore, in its implementation, the TBM Program is expected to expand the choice of reading material menu. Therefore, the determination of reading materials that must be provided needs to take into account the characteristics of the community (including gender, professional age range, etc.), the real needs of the community, community reading ability, and local potential, and supporting physical resources (infrastructure) which are everything needed to support the management of TBM, including bookshelves/cupboards, new book displays, magazine shelves, Newspaper hangers, other facilities for reading such as reading table/bench, mat (mat/carpet) and reading glasses need to be provided. Discussions with partners are carried out by the activity team when the implementation of the activity has begun. What is discussed is about the problems of community life at the location of activities, such as socio-economic problems, work problems, and daily work problems of its residents.